Equine dietary supplements: an insight into their use and perceptions in the Irish equine industry - Murray, J. M. D. (Ir Vet J, 2018)
BACKGROUND: Nutritional supplements are frequently used by horse owners/caregivers to supplement their horse(s) diets. Some work has been done to identify the types of supplements fed and the reasons for doing so; however, this has been predominantly disciple-specific and with little focus on participants’ perceptions of supplement testing and regulation. The aim of this study was to gain an insight into the use and perceptions of equine dietary supplements in the Irish equestrian industry. METHODS: An online survey was designed to ascertain the following information: demographics, types of supplements fed and reasons for use, factors that influenced respondents’ choice of supplement, where advice was sought and perceptions of testing and regulation of equine supplements RESULTS: The survey yielded 134 responses, 70% non-professionals and 30% professionals. A greater percentage of professionals included supplements in their horse(s) diets (98%) compared to non-professionals (86%). Almost 70% of professionals fed more than two supplements, whereas 80% of non-professionals reported to feed only one supplement. Joint supplements were most commonly fed by all respondents (22%) followed by calming supplements (13%). The enhancement of performance (35%) and prevention of joint disorders (34%) were the most common reasons reported by respondents for using a supplement. Over 53% of respondents sought advice on choosing a supplement from their feed merchant, followed by their veterinarian (46%). Veterinary recommendation was given as the most influential factor when choosing a supplement by 90% of respondents, followed by cost (69%). Most (93%) respondents thought that feed supplements had to meet legal standards, with each batch analysed for quality (72%) and the supplement tested on horses before being launched on to the market (92%). CONCLUSION: This study has identified the main types of supplements used in the Irish equestrian industry along with the reasons for their use. However, it has also highlighted major misperceptions in how supplements are tested before being launched for sale and further work on this aspect of the findings would be beneficial.